2006
DOI: 10.1097/01.ftd.0000198648.39751.11
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Dosing of Amoxicillin in (Pre)term Neonates

Abstract: Amoxicillin plasma concentrations, pharmacokinetic parameters, and the influence of demographic, anthropometric, and clinical covariates were investigated in 150 neonates. Gestational age (GA) ranged from 25 to 42 weeks and mean postnatal age (PNA) was 0.8 days. Amoxicillin concentrations were measured with reversed-phase HPLC in surplus plasma from routine assays of coadministered gentamicin. Mean total body clearance corrected for body weight (CL/W) was 0.096 +/- 0.036 L/kg(-1)h(-1), mean elimination half-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 15 publications
3
42
1
Order By: Relevance
“…The most recent study looked at the effects of postnatal age and found that the Cl was greater in neonates >9 days old (3.0 ml min −1 kg −1 ) [17] than had been shown in previous studies in neonates of a similar gestation (1.6 ml min −1 kg −1 ) [15]. Similarly, the t ½ was considerably shorter (3 h vs. 5.2 h).…”
Section: Amoxicillinmentioning
confidence: 89%
See 3 more Smart Citations
“…The most recent study looked at the effects of postnatal age and found that the Cl was greater in neonates >9 days old (3.0 ml min −1 kg −1 ) [17] than had been shown in previous studies in neonates of a similar gestation (1.6 ml min −1 kg −1 ) [15]. Similarly, the t ½ was considerably shorter (3 h vs. 5.2 h).…”
Section: Amoxicillinmentioning
confidence: 89%
“…In one study, the authors recommended a dose of 15 mg kg −1 8 h −1 for GA <34 weeks and 20 mg kg −1 8 h −1 for GA >34 weeks [15]. The authors of the second study suggested that preterm infants with GA <32 weeks in the first week of life should receive a maximum amoxicillin dose of 25 mg kg −1 12 h −1 [13].…”
Section: Amoxicillinmentioning
confidence: 99%
See 2 more Smart Citations
“…Even in neonates, several studies have demonstrated that therapeutic serum levels are easily reached with oral dosing of amoxicillin in term and preterm neonates. 8,9 For the remainder of this review, the published recommendations and available evidence behind the duration of IV therapy are summarized for 4 bacterial infections in children in which IV antibiotic therapy often continues after clinical recovery: meningitis, bacteremia, UTI, and acute osteomyelitis. We conclude by proposing additional considerations for IV antibiotic durations, especially in situations where guidelines and/or evidence are either nonexistent, dated, conflicting, or contrary to evidence from published studies.…”
Section: Extending IV Antibiotics Beyond Clinical Recoverymentioning
confidence: 99%